Methimazole-Induced Goitrogenesis in an Adult Patient With the Syndrome of Resistance to Thyroid Hormone. (13th October 2014) - Glymph, Kathleen; Gosmanov, Aidar R.
Patients with the syndrome of resistance to thyroid hormone (RTH) have clinical (tachycardia and anxiety) and biochemical (elevated thyroid hormones level) features of hyperthyroidism. Based on previous reports in pediatric patients with the RTH, antithyroid treatment in these patients is not indicated. Clinical and biochemical sequel of antithyroid therapy in an adult patient with RTH was not previously reported. A 63-year-old African American female with history of RTH was treated with a therapy consisting of methimazole 15 mg daily and atenolol. Methimazole treatment resulted in reduction in thyroid hormone level while the patient's TSH increased with a peak of 24.88 mIU/L. Having achieved biochemical euthyroidism, the patient developed thyroid gland enlargement associated with progressive symptoms of dysphagia and dyspnea. Examination demonstrated globally enlarged firm thyroid gland with areas of nodularity in both lobes. A computed tomography of the neck showed enlarged thyroid gland with extension around bilateral sternocleidomastoid muscles and compression onto the trachea. Methimazole therapy was discontinued and patient was treated just on atenolol. Over 12 months following discontinuation of methimazole, the patient experienced marked clinical and radiographic improvement of the goiter size associated with TSH reduction to 1.26 mIU/L and modest free thyroxine increase as expected in RTH. It seems appealing to treat patients with the RTH with antithyroid medications. However, in these patients decrease in thyroid hormone levels will stimulate TSH production, which can, in turn, predispose to goiter formation. Our report supports prior observations in children with RTH that treatment with methimazole is not indicated in adult patients with RTH.